PENGARUH EDUKASI MANAJEMEN DIRI TERHADAP DAN TEKANAN DARAH PASIEN HIPERTENSI DI RUANG RAWAT INAP RUMAH SANTA ELISABETH MEDAN - Rusmauli Rusmauli; Connie M Sianipar (STIKes Santa Elisabeth Medan, 2020)
Introduction: The risk for cardiovascular disorder caused by hypertension can be forestalled and controlled by applying healthy behavior such as exercises, cognitive symptom management, healthy diet, and blood pressure monitoring. In this case, education plays an important role in increasing the control of blood pressure. The objective of the research was to identify the influence of self-management education on healthy behavior and blood pressure in hypertension patients in the Hospital Elisabeth Medan Method: The research used quasi experiment and nonequivalent control group pre-post test design. The samples for this study were 60 hypertension patients as the respondents divided into two group, 30 in the intervention group and 30 in the control group taken by consecutive sampling technique. The data were gathered by using modification instruments from Stanford University; they were exercise behavior scale, cognitive symptom scale, questionnaires on healthy diet, and digital Omron tensimeter for measuring blood pressure Result: The data were gathered by using modification instruments from Stanford University; they were exercise behavior scale, cognitive symptom scale, questionnaires on healthy diet, and digital Omron tensimeter for measuring blood pressure. Data were analyzed using descriptive statistics, Wilcoxon and Mann Whitney test. The result of the research showed that there was no influence of self-management education on exercise (p-value = 1.00 > 0.05), there was the influence of self-management education on cognitive symptom (p-value = 0.00 < 0.05), there was the influence of self-management education on healthy diet (p-value = 0.00 < 0.05), and there was the influence of self-management education on systolic and diastolic blood pressure (p-value = 0.00 < 0.05).. Discussion: The conclusion of the research was that education could increase the application of healthy behavior and controlling blood pressure in hypertension patients. The result of the research could be an input for health care to maintain and increase education in hypertension patients so that they could control their blood pressure and forestall hypertension complication.